Analysis of the Effect of Entrepreneurship Education on Entrepreneurial Intentions with Entrepreneurial Motivation and Opportunity Recognition as Intervening Variables - Rika Yuliana; Soepatini Soepatini (International Journal of Management Science and Information Technology, 2024)
Entrepreneurship is pivotal in advancing social and economic development, particularly in enhancing community living standards. A strategic approach is needed to foster entrepreneurship growth. This research aims to analyze the influence of entrepreneurship education on entrepreneurial intention, with entrepreneurial motivation and opportunity recognition as intervening variables. Conducted using a quantitative method, questionnaires were distributed to 221 students from Universitas Muhammadiyah Surakarta and 'Aisyiyah University of Surakarta in November 2023. The relationships between variables were analyzed using smart partial least squares (SPLS). The results indicate that: (1) entrepreneurial motivation positively influences opportunity recognition; (2) entrepreneurship education positively influences entrepreneurial motivation; (3) entrepreneurship education does not influence entrepreneurial intention; (4) entrepreneurship education positively influences opportunity recognition; (5) opportunity recognition positively influences entrepreneurial intention; (6) entrepreneurial motivation positively influences entrepreneurial intention; (7) entrepreneurial motivation mediates the influence of entrepreneurship education on opportunity recognition; (8) entrepreneurial motivation mediates the influence of entrepreneurship education on entrepreneurial intention; (9) opportunity recognition does not mediate the influence of entrepreneurial motivation on entrepreneurial intention; (10) opportunity recognition does not mediate the influence of entrepreneurship education on entrepreneurial intention; (11) entrepreneurial motivation and opportunity recognition do not mediate the influence of entrepreneurship education on entrepreneurial intention.